Preparation method and application of high-capacity resin hard carbon material
The resin hardcarbon materials prepared by epoxy resin and amine curing agents solve the problem of poor electrochemical performance caused by hardcarbon material defects through pre-carbonization, phosphating and high-temperature carbonization treatment, and achieve high capacity and high stability resin hardcarbon materials, which improves the energy density of sodium ion batteries.
Patent Information
- Application Number
- CN202411927455.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-25
- Publication Date
- 2025-03-25
AI Technical Summary
The existing hard charcoal materials have poor efficiency and cycle stability for the first time in sodium ion batteries, mainly due to the large number of surface defects of the material.
The resin-based hardcarbon material is prepared by using epoxy resin and an amine-based curing agent, and is first subjected to pre-carbonization treatment, then phosphating in a phosphoric acid solution, and finally carbonizing at high temperature to form a high-capacity resin-based hardcarbon material.
This method effectively reduces the defects of hard char material, improves its electrochemical performance and cycle stability, and significantly improves the energy density of sodium ion batteries.
Smart Images

Figure CN119683606A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of battery materials, and in particular to a preparation method and application of a high-capacity resin hard carbon material. Background Art
[0002] In recent years, my country's electrochemical energy storage technology has been dominated by lithium-ion batteries. However, due to the rapid growth of new energy vehicles, the price of lithium carbonate has fluctuated frequently and significantly. This phenomenon has posed a challenge to the sustainable and healthy development of the new energy industry to a certain extent. At the same time, my country's current high dependence on imports of lithium salts has also limited the industry's autonomy and development speed.
[0003] Compared with lithium-ion batteries, my country's sodium resource reserves account for 22% of the world's total, with abundant resources and low prices. In addition, sodium-ion batteries have higher internal resistance than lithium-ion batteries, generate less instantaneous heat and have lower temperature rise in safety tests such as short circuits, and have better safety performance. At the same time, sodium-ion batteries have a longer expected service life, are easy to recycle and reuse, and are more conducive to environmental protection. In recent years, the research on the application of hard carbon materials as negative electrode materials in sodium-ion batteries has gradually increased, and they are considered to be the most likely negative electrode materials for sodium-ion batteries to be commercialized.
[0004] Since hard carbon materials contain a large number of defects, they affect the thermodynamics and kinetics of the charge and discharge process, and show poor first coulombic efficiency and cycle stability. Therefore, it is urgent to find a way to modify the defects on the surface of hard carbon materials and improve the electrochemical performance of hard carbon materials as much as possible. Summary of the invention
[0005] In view of the shortcomings of the prior art mentioned above, the purpose of the present invention is to provide a method for preparing a high-capacity resin-based hard carbon material, which is used to solve the problem that the hard carbon material in the prior art has many defects, thereby reducing the first coulombic efficiency and cycle stability of the sodium ion battery; at the same time, the present invention will also provide a high-capacity resin-based hard carbon material obtained by the preparation method; in addition, the present invention will also provide the application of the high-capacity resin-based hard carbon material.
[0006] In order to achieve the above-mentioned object and other related objects, the present invention provides the following technical solutions: The first aspect of the present invention provides a method for preparing a high-capacity resin hard carbon material, comprising the following steps: S1. Using epoxy resin as raw material, introducing an amine curing agent for curing, and placing the cured material under the protection of an inert gas for pre-carbonization treatment to obtain a pre-carbonized material; S2, uniformly dispersing the pre-carbonized material obtained in step S1 in a phosphoric acid solution, and performing a phosphating reaction for a period of time under stirring to obtain a dispersion; S3, filtering the dispersion, washing and drying the filter residue to obtain a phosphating product; S4, placing the phosphating product obtained in step S3 under the protection of an inert gas for carbonization treatment to obtain the high-capacity resin-based hard carbon material.
[0007] The present invention selects epoxy resin as the raw material of hard carbon, introduces amine curing agent for curing, and because the epoxy group of epoxy resin is well developed, the active hydrogen on the nitrogen atom of amine curing agent opens the epoxy group, so that it is cross-linked and cured, and thus the obtained curing material has a well-developed network structure. At the same time, the present invention uses amine curing agent to directly cure epoxy resin, which can avoid introducing catalysts such as acidic medium. The residual and decomposition of the catalyst will reduce the purity of the product, and the subsequent purification treatment will also increase the cost, so the use of amine curing agent for direct curing can effectively control the generation of by-products and reduce the manufacturing cost.
[0008] The present invention places the pre-carbonized solidified material in a phosphoric acid solution and stirs it, so that the defective parts of the pre-carbonized material still adsorb phosphate, which is beneficial to the doping of phosphorus in the subsequent carbonization process, reduces the defects of the hard carbon material, and improves the initial efficiency of the battery. In addition, by further controlling the carbonization temperature and carbonization time, the prepared hard carbon material has the characteristics of being highly disordered and rich in nitrogen. When used as the negative electrode material of the sodium ion battery, it can adsorb more sodium ions, which can greatly improve the energy density of the battery. Preferably, in step S1, the amine curing agent includes at least one of ethylenediamine, hexamethylenediamine, diethylenetriamine, triethylenetetramine, and diethylaminopropylamine.
[0009] Preferably, in step S1, the mass ratio of the epoxy resin to the amine curing agent is 1:(0.1-1). More preferably, the mass ratio of the epoxy resin to the amine curing agent is 1:0.5.
[0010] When the addition amount of amine curing agent is less, epoxy resin is not fully cured, forming a network structure with poor stability, which is not conducive to subsequent carbonization. When the addition amount of amine curing agent is more, it is easy to form too many nitrogen defects on the hard carbon surface, resulting in the generation of irreversible capacity. Therefore, the present invention promotes the good combination between epoxy resin and amine curing agent matrix by controlling the mass ratio of epoxy resin and amine curing agent, forming a uniform and dense network structure, so that the solidified material is suitable for storing sufficient sodium ions after carbonization, and the structural stability of the cycle process is guaranteed on the other hand.
[0011] Preferably, in step S1, the temperature of the pre-carbonization treatment is 400-600°C, and the time of the carbonization treatment is 3-5 hours.
[0012] Preferably, in step S1, the inert gas includes nitrogen, argon or a nitrogen-argon mixed gas.
[0013] Preferably, in step S2, the concentration of the phosphoric acid solution is 0.1-3 mol / L. More preferably, the concentration of the phosphoric acid solution is 1 mol / L.
[0014] Preferably, in step S2, the phosphating reaction time is 6 to 12 hours. More preferably, the phosphating reaction time is 8 to 10 hours.
[0015] The present invention places the pre-carbonized material in a phosphoric acid solution and stirs it, so that the places where the pre-carbonized material still has defects adsorb phosphate, which is beneficial to the doping of phosphorus in the subsequent carbonization process. After phosphorus doping, P=O and PC bonds can be formed between graphite layers, thereby enhancing the adsorption of sodium ions and improving the sodium storage capacity. During the phosphating process, if the solution acidity is too low and the phosphating time is too short, the defects of the pre-carbonized material cannot be completely filled; when the solution acidity is too high and the phosphating time is too long, too much phosphoric acid will remain and by-products are easily generated. Therefore, the present invention controls the amount of phosphoric acid and the stirring time during the phosphating process, so that the phosphate fills the defects of the pre-carbonized material fully, evenly and appropriately. This method has lower cost and is suitable for large-scale industrial production.
[0016] Preferably, in step S3, the phosphating product is washed with deionized water and then transferred to a vacuum oven for drying at a temperature of 80 to 120° C. for a drying time of 24 to 36 hours.
[0017] Preferably, in step S4, the temperature of the carbonization treatment is 1200-1600° C., the carbonization time is 2-3 h, and the heating rate is 3-5° C. / min.
[0018] Preferably, in step S4, the inert gas includes nitrogen, argon or a nitrogen-argon mixed gas.
[0019] The second aspect of the present invention provides a high-capacity resin hard carbon material, which is prepared by the above-mentioned preparation method.
[0020] In a third aspect of the present invention, there is provided a negative electrode plate, wherein the negative electrode plate adopts the high-capacity resin hard carbon material prepared as above as the negative electrode active material, and the negative electrode plate is prepared by the following steps: T1. Mixing a high-capacity resin hard carbon material, a conductive agent and a binder in proportion to prepare a negative electrode slurry; T2. Coating the negative electrode slurry on the current collector and drying it to obtain the negative electrode sheet.
[0021] Preferably, in step T1, the mass ratio of the hard carbon material, the conductive agent and the binder is (7-8): (2-1): 1. More preferably, the mass ratio of the hard carbon material, the conductive agent and the binder is 7:2:1 or 8:1:1.
[0022] Preferably, in step T1, the conductive agent includes conductive carbon black. The binder includes any one of sodium carboxymethyl cellulose (CMC), polyvinylidene fluoride (PVDF), and sodium alginate; preferably sodium carboxymethyl cellulose (CMC). The solvent used for polyvinylidene fluoride (PVDF) is N-methyl pyrrolidone (NMP); the solvent used for sodium carboxymethyl cellulose (CMC) and sodium alginate is water.
[0023] Preferably, in step T2, the current collector is copper foil or aluminum foil. More preferably, the current collector is aluminum foil.
[0024] Preferably, in step T2, the drying temperature is 80-120° C., and the drying time is 12-24 hours.
[0025] According to a fourth aspect of the present invention, a sodium ion battery is provided, comprising a negative electrode, a positive electrode, a separator and an electrolyte, wherein the negative electrode adopts the negative electrode plate mentioned above.
[0026] Preferably, the electrolyte comprises a sodium salt and a non-aqueous solvent. The sodium salt is any one of NaClO4 and NaPF6; the non-aqueous solvent is any one or a combination of ethylene carbonate (EC), diethyl carbonate (DEC), propylene carbonate (PC), and dimethyl carbonate (DMC). In the electrolyte, the concentration of the sodium salt is 0.8-1.5 mol / L.
[0027] More preferably, when the sodium salt is NaClO4, the non-aqueous solvent is a mixture of EC and DEC in a volume ratio of 1:1, or the non-aqueous solvent is PC; when the sodium salt is NaPF6, the non-aqueous solvent is a mixture of EC, DMC and DEC in a volume ratio of 1:1:1, or the non-aqueous solvent is a mixture of EC and PC in a volume ratio of 1:1.
[0028] As described above, the preparation method and application of a high-capacity resin hard carbon material of the present invention have the following beneficial effects: 1. The present invention selects epoxy resin, which is abundant in resources, widely available, and environmentally friendly, as the raw material of hard carbon, which has low cost and low energy consumption. In addition, since the epoxy resin has a well-developed network structure after curing, by controlling the carbonization temperature and carbonization time, the hard carbon material prepared has the characteristics of being highly disordered and rich in nitrogen. When used as the negative electrode material of the sodium ion battery, it can absorb more sodium ions, which can greatly improve the energy density of the battery.
[0029] 2. The present invention controls the mass ratio of epoxy resin to amine curing agent to promote good bonding between epoxy resin and amine curing agent matrix to form a uniform and dense network structure, which not only makes the curing material more suitable for storing sufficient sodium ions after carbonization, but also ensures the structural stability of the circulation process.
[0030] 3. The present invention places the pre-carbonized material in a phosphoric acid solution and stirs it, so that phosphate is adsorbed on the defective parts of the pre-carbonized material, which is beneficial to the doping of phosphorus in the subsequent carbonization process; and by controlling the amount of phosphoric acid and the reaction time in the phosphating reaction, the phosphate can fully, evenly and appropriately fill the defects of the pre-carbonized material. This method has lower cost and is suitable for large-scale industrial production.
[0031] 4. The preparation method of the present invention is simple to operate and has a short process flow, and is suitable for large-scale industrial production; the prepared hard carbon material has the characteristics of low defects and high stability, and can be applied to sodium ion batteries to ensure the integrity of the electrode and ensure good cycle stability and electrochemical performance of the battery. BRIEF DESCRIPTION OF THE DRAWINGS
[0032] Figure 1 This is a SEM image of the high-capacity resin-based hard carbon material prepared in Example 2 of the present invention.
[0033] Figure 2 This is the first coulombic efficiency diagram of the sodium ion battery prepared in Example 2 of the present invention.
[0034] Figure 3 This is a cycle performance diagram of the sodium ion battery prepared in Example 2 of the present invention. DETAILED DESCRIPTION
[0035] The following is a description of the implementation of the present invention by means of specific embodiments. Those skilled in the art can easily understand other advantages and effects of the present invention from the contents disclosed in this specification.
[0036] Example 1 A method for preparing a high-capacity resin hard carbon material comprises the following steps: S1. Place 10 g of epoxy resin in a beaker, add 1 g of amine curing agent while stirring, and after the liquid is completely cured, move it to a tubular furnace, and heat it to 500 ° C at a heating rate of 5 ° C / min under a nitrogen protective atmosphere and calcine it for 4 hours to obtain a pre-carbonized material; S2. Take 1 g of the pre-carbonized material obtained in step S1 and transfer it to a beaker, add 1 mol / L phosphoric acid solution to disperse it, and stir for 8 h to obtain a dispersion; S3, filtering the dispersion in step S2, washing with deionized water to remove excess impurities, and then placing the filter residue in a vacuum oven and drying at 100° C. for 24 hours to obtain a phosphating material; S4. Move the phosphating material of step S3 into a tubular furnace, and heat it to 1400° C. at a heating rate of 5° C. / min under a nitrogen protective atmosphere, and calcine it for 2 hours to obtain a high-capacity resin hard carbon material.
[0037] The high-capacity resin hard carbon material prepared above is used as the negative electrode active material, and is evenly mixed with sodium carboxymethyl cellulose (CMC) and conductive carbon black in a mass ratio of 8:1:1, and an aqueous solvent is added to prepare a negative electrode slurry, which is then coated on aluminum foil and dried in a vacuum drying oven at 100°C for 12 hours. The negative electrode sheet is obtained by rolling and punching.
[0038] Using Na sheet as the counter electrode, the negative electrode sheet obtained above was assembled into a 2032 button cell in a glove box with an argon protective atmosphere where the water and oxygen contents were both less than 0.1 ppm. The sodium salt in the electrolyte used was NaClO4 with a concentration of 1 mol / L, and the non-aqueous solvent was a mixture of EC and DEC with a volume ratio of 1:1.
[0039] After testing, at 27°C and a current density of 30mA / g, the first cycle charging capacity was 280.1mAh / g and the first coulombic efficiency was 82.1%.
[0040] Example 2 A method for preparing a high-capacity resin hard carbon material comprises the following steps: S1. Place 10 g of epoxy resin in a beaker, add 5 g of amine curing agent while stirring, and after the liquid is completely cured, move it to a tubular furnace, and heat it to 500 ° C at a heating rate of 5 ° C / min under a nitrogen protective atmosphere and calcine for 4 hours to obtain a pre-carbonized material; S2. Take 1 g of the pre-carbonized material obtained in step S1 and transfer it to a beaker, add 1 mol / L phosphoric acid solution to disperse it, and stir for 8 h to obtain a dispersion; S3, filtering the dispersion of step S2, washing with deionized water to remove excess impurities, and then placing in a vacuum oven and drying at 100° C. for 24 hours to obtain a phosphating material; S4, moving the phosphating material of step S3 into a tubular furnace, heating the material to 1400° C. at a heating rate of 5° C. / min under a nitrogen atmosphere, and calcining the material for 2 hours to obtain a high-capacity resin hard carbon material; The high-capacity resin hard carbon material prepared above is used as the negative electrode active material, and is evenly mixed with sodium carboxymethyl cellulose (CMC) and conductive carbon black in a mass ratio of 8:1:1, and an aqueous solvent is added to prepare a negative electrode slurry, which is then coated on aluminum foil and dried in a vacuum drying oven at 100°C for 12 hours. The negative electrode sheet is obtained by rolling and punching.
[0041] Using Na sheet as the counter electrode, the negative electrode sheet obtained above was assembled into a 2032 button cell in a glove box with an argon protective atmosphere where the water and oxygen contents were both less than 0.1 ppm. The sodium salt in the electrolyte used was NaClO4 with a concentration of 1 mol / L, and the non-aqueous solvent was a mixture of EC and DEC with a volume ratio of 1:1.
[0042] After testing, at 27°C and a current density of 30mA / g, the first cycle charging capacity was 340.4mAh / g, and the first coulombic efficiency was 93.5%; at a current density of 300mA / g, the battery could cycle 200 times.
[0043] Example 3 A method for preparing a high-capacity resin hard carbon material comprises the following steps: S1. Place 10 g of epoxy resin in a beaker, add 10 g of amine curing agent while stirring, and after the liquid is completely cured, move it to a tubular furnace, and heat it to 500 ° C at a heating rate of 5 ° C / min under a nitrogen protective atmosphere and calcine for 4 hours to obtain a pre-carbonized material; S2. Take 1 g of the pre-carbonized material obtained in step S1 and transfer it to a beaker, add 1 mol / L phosphoric acid solution to disperse it, and stir for 8 h to obtain a dispersion; S3, filtering the dispersion of step S2, washing with deionized water to remove excess impurities, and then placing in a vacuum oven and drying at 100° C. for 24 hours to obtain a phosphating material; S4, moving the phosphating material of step S3 into a tubular furnace, heating the material to 1400° C. at a heating rate of 5° C. / min under a nitrogen atmosphere, and calcining the material for 2 hours to obtain a high-capacity resin hard carbon material; The high-capacity resin hard carbon material prepared above is used as the negative electrode active material, and is evenly mixed with sodium carboxymethyl cellulose (CMC) and conductive carbon black in a mass ratio of 8:1:1, and an aqueous solvent is added to prepare a negative electrode slurry, which is then coated on aluminum foil and dried in a vacuum drying oven at 100°C for 12 hours. The negative electrode sheet is obtained by rolling and punching.
[0044] Using Na sheet as the counter electrode, the negative electrode sheet obtained above was assembled into a 2032 button cell in a glove box with an argon protective atmosphere where the water and oxygen contents were both less than 0.1 ppm. The sodium salt in the electrolyte used was NaClO4 with a concentration of 1 mol / L, and the non-aqueous solvent was a mixture of EC and DEC with a volume ratio of 1:1.
[0045] After testing, at 27°C and a current density of 30mA / g, the first-cycle charging capacity was 291.4mAh / g and the first coulombic efficiency was 86.7%.
[0046] Example 4 A method for preparing a high-capacity resin hard carbon material comprises the following steps: S1. Place 10 g of epoxy resin in a beaker, add 5 g of amine curing agent while stirring, and after the liquid is completely cured, move it to a tubular furnace, and heat it to 500 ° C at a heating rate of 5 ° C / min under a nitrogen protective atmosphere and calcine for 4 hours to obtain a pre-carbonized material; S2. Take 1 g of the pre-carbonized material obtained in step S1 and transfer it to a beaker, add a phosphoric acid solution containing 0.1 mol / L phosphoric acid to disperse it, and stir for 6 hours to obtain a dispersion; S3, filtering the dispersion of step S2, washing with deionized water to remove excess impurities, and then placing in a vacuum oven and drying at 100° C. for 24 hours to obtain a phosphating material; S4, moving the phosphating material of step S3 into a tubular furnace, heating the material to 1400° C. at a heating rate of 5° C. / min under a nitrogen atmosphere, and calcining the material for 2 hours to obtain a high-capacity resin hard carbon material; The high-capacity resin hard carbon material prepared above is used as the negative electrode active material, and is evenly mixed with sodium carboxymethyl cellulose (CMC) and conductive carbon black in a mass ratio of 8:1:1, and an aqueous solvent is added to prepare a negative electrode slurry, which is then coated on aluminum foil and dried in a vacuum drying oven at 100°C for 12 hours. The negative electrode sheet is obtained by rolling and punching.
[0047] Using Na sheet as the counter electrode, the negative electrode sheet obtained above was assembled into a 2032 button cell in a glove box with an argon protective atmosphere where the water and oxygen contents were both less than 0.1 ppm. The sodium salt in the electrolyte used was NaClO4 with a concentration of 1 mol / L, and the non-aqueous solvent was a mixture of EC and DEC with a volume ratio of 1:1.
[0048] After testing, at 27°C and a current density of 30mA / g, the first-cycle charging capacity was 301.3mAh / g and the first coulombic efficiency was 89.5%.
[0049] Example 5 A method for preparing a high-capacity resin hard carbon material comprises the following steps: S1. Place 10 g of epoxy resin in a beaker, add 5 g of amine curing agent while stirring, and after the liquid is completely cured, move it to a tubular furnace, and heat it to 500 ° C at a heating rate of 5 ° C / min under a nitrogen protective atmosphere and calcine for 4 hours to obtain a pre-carbonized material; S2. Take 1 g of the pre-carbonized material obtained in step S1 and transfer it to a beaker, add 3 mol / L phosphoric acid solution to disperse it, and stir for 12 h to obtain a dispersion; S3, filtering the dispersion of step S2, washing with deionized water to remove excess impurities, and then placing in a vacuum oven and drying at 100° C. for 24 hours to obtain a phosphating material; S4, moving the phosphating material of step S3 into a tubular furnace, heating the material to 1400° C. at a heating rate of 5° C. / min under a nitrogen atmosphere, and calcining the material for 2 hours to obtain a high-capacity resin hard carbon material; The high-capacity resin hard carbon material prepared above is used as the negative electrode active material, and is evenly mixed with sodium carboxymethyl cellulose (CMC) and conductive carbon black in a mass ratio of 8:1:1, and an aqueous solvent is added to prepare a negative electrode slurry, which is then coated on aluminum foil and dried in a vacuum drying oven at 100°C for 12 hours. The negative electrode sheet is obtained by rolling and punching.
[0050] Using Na sheet as the counter electrode, the negative electrode sheet obtained above was assembled into a 2032 button cell in a glove box with an argon protective atmosphere where the water and oxygen contents were both less than 0.1 ppm. The sodium salt in the electrolyte used was NaClO4 with a concentration of 1 mol / L, and the non-aqueous solvent was a mixture of EC and DEC with a volume ratio of 1:1.
[0051] After testing, at 27°C and a current density of 30mA / g, the first-cycle charging capacity was 324.6mAh / g and the first coulombic efficiency was 90.7%.
[0052] Comparative Example 1 A method for preparing a resin hard carbon material comprises the following steps: S1. Place 10 g of epoxy resin in a beaker, add 5 g of amine curing agent and 1 g of phosphoric acid while stirring, and after the liquid is completely cured, move it to a tubular furnace, and heat it to 500 ° C at a heating rate of 5 ° C / min under a nitrogen protective atmosphere and calcine it for 4 hours to obtain a pre-carbonized material; S2. Take 1 g of the pre-carbonized material obtained in step S1 and transfer it to a beaker, add pure water and stir for 8 hours to disperse it to obtain a dispersion; S3, filtering the dispersion of step S2, washing with deionized water to remove excess impurities, and then placing in a vacuum oven and drying at 100° C. for 24 h to obtain a purified material; S4, moving the purified material of step S3 into a tubular furnace, heating the temperature to 1400° C. at a heating rate of 5° C. / min under a nitrogen protective atmosphere, and calcining the temperature for 2 h to obtain a resin hard carbon material; The high-capacity resin hard carbon material prepared above is used as the negative electrode active material, and is evenly mixed with sodium carboxymethyl cellulose (CMC) and conductive carbon black in a mass ratio of 8:1:1, and an aqueous solvent is added to prepare a negative electrode slurry, which is then coated on aluminum foil and dried in a vacuum drying oven at 100°C for 12 hours. The negative electrode sheet is obtained by rolling and punching.
[0053] Using Na sheet as the counter electrode, the negative electrode sheet obtained above was assembled into a 2032 button cell in a glove box with an argon protective atmosphere where the water and oxygen contents were both less than 0.1 ppm. The sodium salt in the electrolyte used was NaClO4 with a concentration of 1 mol / L, and the non-aqueous solvent was a mixture of EC and DEC with a volume ratio of 1:1.
[0054] After testing, at 27°C and a current density of 30mA / g, the first cycle charging capacity was 280.5mAh / g, and the first coulombic efficiency was 80.6%; at a current density of 300mA / g, the battery could cycle 100 times.
[0055] From the test results of the above five embodiments and comparative example 1, it can be seen that the performance of the resin hard carbon material prepared in embodiment 2 is the best.
[0056] Comparing Example 2 with Examples 1 and 3, it can be seen that the amount of amine curing agent added in step S1 will affect the formation of the epoxy resin network structure, and further affect the electrochemical properties of the resin hard carbon material. This is because when the amount of amine curing agent added is small, the epoxy resin is not fully cured, forming a network structure with poor stability, which is not conducive to subsequent carbonization; when the amount of amine curing agent added is large, it is easy to form too many nitrogen defects on the surface of the hard carbon, resulting in the generation of irreversible capacity. Therefore, the present invention controls the mass ratio of epoxy resin to amine curing agent to promote good bonding between the epoxy resin and the amine curing agent matrix to form a uniform and dense network structure, so that the cured material is suitable for storing sufficient sodium ions after carbonization, and on the other hand, it ensures the structural stability of the cycle process. The optimal mass ratio of epoxy resin to amine curing agent is 1:0.5.
[0057] Comparing Example 2 with Examples 4 and 5, it can be seen that the concentration of phosphoric acid and the phosphating time in step S2 will affect the generation of defects in the hard carbon material. During the phosphating process, phosphate will be adsorbed in places where the pre-carbonized material still has defects. When the acidity of the solution is too low and the time is too short, the defects cannot be completely filled; when the acidity is too high and the time is too long, too much phosphoric acid will remain, and by-products are likely to be produced. Therefore, it is necessary to control the concentration of phosphoric acid and the phosphating time to promote the good combination of phosphate and pre-carbonized materials, so that the hard carbon material is suitable for storing sufficient sodium ions on the one hand, and on the other hand, to ensure the structural stability of the circulation process. Most preferably, the concentration of phosphoric acid is 1 mol / L and the phosphating time is 8h. In addition, the method of controlling the amount of phosphoric acid and the stirring time is more cost-effective and easy to achieve large-scale industrial production.
[0058] Comparing Example 2 with Comparative Example 1, it can be seen that the phosphoric acid added in the curing stage of Comparative Example 1 will remain in the curing material for pre-carbonization and carbonization. The uneven accumulation of phosphoric acid in the material will not only fail to make up for the defects of the material, but also affect the purity of the material and destroy the structure of the hard carbon material formed. The present invention uses an amine curing agent to directly cure the epoxy resin, avoiding the introduction of an acidic medium to reduce the purity of the material; and by placing the pre-carbonized material in a phosphoric acid solution and stirring it, the pre-carbonized material still has defective places that adsorb phosphate, which is beneficial to the doping of phosphorus in the subsequent carbonization process. After phosphorus doping, P=O and PC bonds can be formed between graphite layers, thereby enhancing the adsorption of sodium ions and improving the sodium storage capacity.
[0059] In summary, the present invention first uses epoxy resin to achieve resin curing through an amine curing agent, and the cured material is subjected to low-temperature carbonization treatment to obtain a pre-carbonized material, and then a phosphoric acid solution is used to phosphate the pre-carbonized material, and finally a high-capacity resin hard carbon material is obtained by high-temperature carbonization. The present invention utilizes the developed network structure after epoxy resin curing, and controls the carbonization temperature and carbonization time to prepare a highly disordered, pore-rich hard carbon material; at the same time, by controlling the addition amount of amine curing agent and phosphoric acid, nitrogen and phosphorus elements are simultaneously doped in the hard carbon material structure to reduce material defects, so that the prepared hard carbon material has good electrochemical properties and cycle stability. Therefore, the present invention effectively overcomes the various shortcomings of the prior art and has a high industrial utilization value.
[0060] The above embodiments are merely illustrative of the principles and effects of the present invention, and are not intended to limit the present invention. Anyone familiar with the art may modify or alter the above embodiments without departing from the spirit and scope of the present invention. Therefore, all equivalent modifications or alterations made by a person of ordinary skill in the art without departing from the spirit and technical concept disclosed by the present invention shall still be covered by the claims of the present invention.
Claims
1. A method for preparing a high-capacity resin hard carbon material, characterized in that: The following steps are involved: S1. Using epoxy resin as raw material, introducing an amine curing agent for curing, and placing the cured material under the protection of an inert gas for pre-carbonization treatment to obtain a pre-carbonized material; S2, uniformly dispersing the pre-carbonized material obtained in step S1 in a phosphoric acid solution, and performing a phosphating reaction for a period of time under stirring to obtain a dispersion; S3, filtering the dispersion, washing and drying the filter residue to obtain a phosphating product; S4, placing the phosphating product obtained in step S3 under the protection of an inert gas for carbonization treatment to obtain the high-capacity resin-based hard carbon material.
2. The method for preparing a high-capacity resin hard carbon material according to claim 1, characterized in that: In step S1, the amine curing agent includes at least one of ethylenediamine, hexamethylenediamine, diethylenetriamine, triethylenetetramine, and diethylaminopropylamine.
3. The method for preparing a high-capacity resin hard carbon material according to claim 2, characterized in that: The mass ratio of epoxy resin to amine curing agent is 1:(0.1~1).
4. The method for preparing a high-capacity resin hard carbon material according to claim 1, characterized in that: In step S1, the temperature of the pre-carbonization treatment is 400-600°C, and the time of the carbonization treatment is 3-5 hours.
5. The method for preparing a high-capacity resin hard carbon material according to claim 1, characterized in that: In step S2, the concentration of the phosphoric acid solution is 0.1-3 mol / L.
6. The method for preparing a high-capacity resin hard carbon material according to claim 1, characterized in that: In step S2, the phosphating reaction time is 6 to 12 hours.
7. The method for preparing a high-capacity resin hard carbon material according to claim 1, characterized in that: In step S4, the temperature of the carbonization treatment is 1200-1600°C, the carbonization time is 2-3h, and the heating rate is 3-5°C / min.
8. A high-capacity resin hard carbon material, characterized in that: The high-capacity resin hard carbon material is prepared by the preparation method of any one of claims 1 to 7.
9. A negative electrode plate, characterized in that: The negative electrode plate adopts the high-capacity resin hard carbon material as claimed in claim 8 as the negative electrode active material, and the negative electrode plate is prepared by the following steps: T1. Mixing a high-capacity resin hard carbon material, a conductive agent and a binder in proportion to prepare a negative electrode slurry; T2. Coating the negative electrode slurry on the current collector and drying it to obtain the negative electrode sheet.
10. A sodium ion battery comprising a negative electrode, a positive electrode, a separator and an electrolyte, characterized in that: The negative electrode adopts the negative electrode sheet according to claim 9.
Citation Information
Cited By
Phenolic resin-based hard carbon material as well as preparation method and application thereof
CN121376973A